Il movimento scenico nel teatro sperimentale degli anni Settanta - Lorenzo Mango (Danza e Ricerca, 2023)
The 1970s in Italian theatre were characterised by a strong tension towards performativity, which challenged the representative stage code. In this context, the function of the body as a stage presence was redefined. Movement, understood as the action of the body in space, became central. Significant in this respect is what happened in the post-avant-garde and, in particular, in the work of Federico Tiezzi's Carrozzone and La Gaia scienza of Giorgio Barberio Corsetti, Marco Solari and Alessandra Vanzi. In this case, we have a non-referential action that dissolves into a real choreography that tends towards abstraction on the one hand and towards the solute concreteness of the stage act on the other. Movement is in fact treated as the analytical writing of a physical action, through a system of gestures that relate body and space.